Income redistribution - Campbell, Colin Dearborn; American Enterprise Institute for Public Policy Research; Hoover Institution on War, Revolution, and Peace (Washington : American Enterprise Institute for Public Policy Research, 1977)
This book contains proceedings presented at a conference held in Washington, D.C. from May 20 to May 21, 1976 and sponsored by the American Enterprise Institute for Public Policy Research and the Hoover Institution on War, Revolution, and Peace.
Papers presented at a conference held in Washington, D.C. from May 20 to May 21, 1976 and sponsored by the American Enterprise Institute for Public Policy Research and the Hoover Institution on War, Revolution, and Peace.
Includes bibliographical references.
osa 03/07/2017
Loans
Keywords: Income distribution; Income distribution - United States - Congresses; United States